Natural gas reservoirs on the oil-gas fild Petišovci - Jernej Kerčmar (Geologija, 2018)
Three conditions are required for the existence of hydrocarbon reservoirs: source rock (usually basement or footwall), collector (porous rock in which the hydrocarbons are caught), and upper impermeable rock (hanging wall). In addition to a geological structure, temperature, pressure and time are needed for the organic matter to pass through the diagenesis phase into hydrocarbons, as we know them today. Every hydrocarbon deposit found and having economical reserves for production passes fie stages of the life cycle of the reservoir. First, geological, geophysical, petrophysical and reservoir exploration is carried out, and then results of these explorations are evaluated by 2D and 3D geological models. Next stage is evaluation of entire fild potential (in-place) and proved reserves of all hydrocarbons-bearing reservoir strata (reservoirs). Afterwards, the most important stage is production and the end phase with the remediation of the fild. In Slovenia, most of the natural gas was produced from the “Petišovci globoko” reservoirs in the years between 1963 and 2017, totaling to more than 341 million Sm3. In recent years, the fild has been further developed by processing prospective natural gas reservoirs in socalled ‘K’ series (“Petišovci globoko”). Since 2017, the production of gas from two new wells, Pg-10 and Pg-11A, takes place.